ANALISIS PELAKSANAAN PROGRAM USAHA KESEHATAN SEKOLAH (UKS) DI SD NEGERI TLOGOSARI KULON 01 SEMARANG - Ela Atika, Asep Ardiyanto, dan Ferina Agustini (Universitas PGRI Yogyakarta, 2020)
AbstractHealth education through School Health Unit is important and must be encouraged. This research aims to observe, try to analyze, describe and evaluate the implementation of the School Health Unit program in elementary school. This type of research was a descriptive qualitative research. Sources of data obtained through interview, observation, questionnaires, and documentation. The result of the research that implementation of the School Health Unit program, some have going to plan, but there are some indicators of School Health Unit success that have yet to be implemented, such as the absence of a decision letter by the implementasion team, don’t have budget planning, healthy school canteen control by the physical Education teachers or community health centers should be further improved, classroom density, non-smoking areas. In the implementation of the School Health Unit program monitoring activities haven’t been carried out according to instruments, reporting hasn’t beeb carried out according to the corect format, and evaluation techniques haven’t been carried out according to the rules.Keywoards: School Health Unit, Health Education, Three School Health Unit Programs.